Comprehensive assessment of organic Rankine cycles using renewables energy for combined power and heat generation in a badminton stadium - Jiaojiao Liu; Zhanguo Su (Case Studies in Thermal Engineering)
Regarding to higher rate of energy consumption in sport facilities, paying to the energy and energy production ways to consume in these spaces has become a necessity. Therefore, finding innovative ways for energy production applying renewable sources and free pollutant as well as efficiency increase is significant. Consumption of the ORC cycle applying geothermal energy resource is one of the methods of energy production. Therefore, this study attempted to investigate the production of ORC cycle power and increase of power production which is concerned via concentration on the dual pressure cycle. When the ambient and heat source temperatures change, the system performance becomes undesirable. The dual-pressure ORC was evaluated under non-ideal conditions by changing the heat source and ambient temperatures to report the performance and stability of the system in power generation. Compared to the baseline-ORC, the results show that the dual-pressure ORC works properly. In all conditions, the exergy efficiency and power generation of the dual-pressure ORC are higher than the baseline, which are 21 and 24 %, respectively. The evaporation process undergoes large changes with the temperature of the heat source as the ambient temperature changes, the mass flow rate of the working fluid, and the evaporation process. 70 % of the system's power generation is related to the low-pressure turbine. By changing the effective parameters, a significant drop in production is observed, so by optimizing the low-pressure turbine, the system performance is improved.